Investigation of nanoparticles Cu, Ag and Fe3O4 on thermophoresis and viscous dissipation of MHD nanofluid over a stretching sheet in a porous regime: A numerical modeling - Hazarika, Silpi; Ahmed, Sahin; Chamkha, Ali J. (Mathematics and computers in simulation, 2021)
This article provides insight into the study of hydromagnetic flow of a chemically reacting water based nanofluid of Copper (Cu), Silver (Ag) and Ferrous Ferric Oxide (Fe3O4) nanoparticles over a stretching permeable sheet with heat generation, nanoparticle volume fraction, Soret number, Eckert number and porosity. The governing system of PDEs is reduced to nonlinear ODEs by the tool of similarity transformations, and is solved by fourth order Runge–Kutta scheme with the shooting method via MATLAB. Output of the nanofluid velocity, temperature and concentration for the involved material parameters as well as the correlated engineering physical quantities like coefficient of skin friction and rate of heat transfer are demonstrated via single plots of three nanopartciles and Tables. Heat generation and Soret number for three different nanoparticles play a significant role throughout the investigation. Greater nanoparticle volume fraction decreases the liquid velocity, while a non-decline situation has occurred for liquid temperature. Furthermore, the velocity always overshoots for Fe3O4 -water nanofluid, followed by Cu and Ag–water nanofluid, whereas the reverse performance is observed for the temperature profiles. An excellent validation of this model is accomplished. The adopted numerical scheme of RK-Shooting is stable and convergent in the same domain throughout the numerical calculations. The proposed investigation shows the importance of three nanoparticles in medical industry and biocompatibility engineering. Also, these nanoparticles can be used in physics, engineering, space technology, high temperature and cooling process, medicines, biosensors, paints, cosmetics, conductive coatings and medical devices. •Impact of Fe3O4, Cu and Ag for water based nanofluid in porous regime is studied.•4th order RK-Shooting Technique have been employed to solve the non-linear PDE.•Significant impact has been observed due to various conductivity of the nanoparticles.•Importance of these nanoparticles can be found in medical industry & bio-engineering.